Organ transplants as commodities? - Zwart, Hub (Henry Stewart Talks, 2015)
Transplantation medicine and embodiment, Bioethics and ‘depth ethics’: ontological repercussions of organ transplants, Bodily integrity (the inviolable body) vs. the body as an aggregate of replaceable parts, Organ transplant cinema: organ theft